The Impact of the New Translation of The Second Sex: Rediscovering Beauvoir. - Daigle, Christine (Journal of Speculative Philosophy, 2013)
An essay is presented that discusses the 1952 translation from French to English of the book "Le deuxième sexe," by Simone de Beauvoir, by zoologist Howard M. Parshley as "The Second Sex." The 2009 translation of the book by translators Constance Borde and Sheila Malovany-Chevallier is noted. Problems with both translations are noted in light of the influence of the book.